Building Infrastructure and Capacity for Correctional Health Research in a College of Criminal Justice: Lessons and Promises. (March 2016) - Sung, Hung-En; Mellow, Jeff; Vaughan, Roger D.; Drucker, Ernest
This analysis describes the planning and implementation of a development project to build infrastructure and capacity for correctional and community health research in a college of criminal justice. Partnering with a research-intensive university, the 3-year project recruited 112 faculty and student trainees for mentored research, extramural and intramural training, subsidized conference travels, and new course offerings. A network of 34 "nuclear" investigators emerged as a cohesive infrastructure from the experience, producing 21 refereed publications, 18 conference presentations, and nine grant applications in correctional and community health. A sustainability plan has been executed to consolidate the gains achieved. Lessons are discussed.